Proceeding Bromometric Phenol Assay without Starch Indicator - Q. Abdulkadir, Maadh (Iraqi Journal of Pharmaceutical Sciences, 2017)
In this research, we exclude starch indicator preparation,that is used in official phenol assay method. The liberated iodine, in presence of chloroform, was acting as indicator and titrated with sodium thiosulfate until getting a sharp colorless end point. Similarly, starch was cancelled during both blank and standardization of bromine water solution experiments needed in phenol assay. The results obtained were the same volumes and weights as that achieved using starch with just about 0.03% difference in sample procedure. Finally, this work will enable us to save time, effort, fuel and materials spended in laboratory.Key word:- Phenol, assay, starch indicator